Targeting N-type calcium channels in young-onset of some neurological diseases - Antunes, Flavia Tasmin Techera; De Souza, Alessandra Hubner; Figueira, Juliana; Binda, Nancy Scardua; Carvalho, Vanice Paula Ricardo; Vieira, Luciene Bruno; Gomez, Marcus Vinícius (Frontiers in Cell and Developmental Biology, 2022)
Calcium (Ca2+) is an important second messenger in charge of many critical processes in the central nervous system (CNS), including membrane excitability, neurotransmission, learning and memory, cell proliferation, and apoptosis. In this way, voltage-gated calcium channels (VGCCs) act as a key supply for Ca2+ entry into the cytoplasm and organelles. Importantly, the deregulation of those channels has been reported in a number of neurological diseases of young onset with genetic factors associated, such as migraine, multiple sclerosis, and Huntington's disease. Notably, literature has pointed to the role of N-type Ca2+ channels (NTCCs) in controlling a variety of processes, including pain, inflammation, and excitotoxicity. Moreover, several Ca2+ channel blockers used for therapeutic purposes have been shown to act on N-type channels. Therefore, this review provides an overview of NTCCs in neurological disorders with young onset, focusing mainly on Huntington's disease, multiple sclerosis, and migraine plus discusses possible strategies to generate novel therapeutics strategies.